Analysis Of Customer Satisfaction With Solaria Restaurants In Medan City Using K-Means Clustering Method - Marpaung, Udur Mega; -, Anita; Gulo, Sapriliyani (Jurnal Sistem Informasi dan Ilmu Komputer, 2024)
Customer satisfaction is the key to the success of a company in the modern business context. In strategic planning and business management, a focus on customer satisfaction has become essential to ensure that the services a company provides not only retain customers but also enable sustainable growth. In the case of Solaria Restaurant, it helps to find groups of customers with comparable satisfaction patterns, which allows businesses to optimize their marketing strategies and improve their service quality. Specifically, this study uses the K-Means Clustering method to evaluate customer satisfaction with Solaria Restaurant services. The research utilized an online questionnaire distributed to 250 surveyed people to assess factors such as service response and the physical appearance of the restaurant that affect customers' perceptions of the business. The results showed that customer satisfaction is generally considered very good, the results of clustering analysis of customer satisfaction at Solaria Restaurant resulted in the number of very good clusters is cluster I. This result increases our understanding of customer preferences. These results increase our understanding of customer preferences and build a basis for improvement strategies that focus more on improving the customer experience.